2016
DOI: 10.1177/1757975915602187
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between new media exposure and fast food consumption among Chinese children and adolescents in school: a rural–urban comparison

Abstract: This paper suggests that monitoring the nutritional effects of new media exposure in China is of key importance in order to develop adequate health promotion policies, in both rural and urban areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
2
12
1
Order By: Relevance
“…These results were consistent with prior study [ 31 ] that showed children who reside in rural areas spend more time online and are more vulnerable to online risks. However, this study found no differences between urban and rural areas in China, which is a result that differs from that of prior study [ 32 ]. The reason may be due to the sample schools in China being located in the same province and possibly having similar living resources.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results were consistent with prior study [ 31 ] that showed children who reside in rural areas spend more time online and are more vulnerable to online risks. However, this study found no differences between urban and rural areas in China, which is a result that differs from that of prior study [ 32 ]. The reason may be due to the sample schools in China being located in the same province and possibly having similar living resources.…”
Section: Discussioncontrasting
confidence: 99%
“…China has the world’s largest population, and China’s one-child policy and culturally inflected social control experiences could have had an impact on children’s internet use and online risks [ 30 ]. Prior studies conducted in China and Taiwan have indicated that children and adolescents who reside in rural areas spend more time playing online games and are more vulnerable to online risks such as cyber victimization compared with their urban counterparts [ 31 , 32 ]. Despite studies have associated young adult and adolescent problematic gaming behaviors and internet addictions with online risks and psychological distress [ 33 35 ], only a limited amount of research has explored the relationships between children’s gaming preferences and online risks, and exploring the links to the possible psychological impact.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, males reported a greater fast-food consumption compared with females [43]. More recently, an elegantly designed cross-sectional study also found strong evidence for the influence of new media exposure to fast-food consumption among Chinese children and adolescents aged between six and 18 [44]. The study showed that watching online videos and playing computer games are behaviors associated with higher probabilities of eating at fast food restaurants in both rural and urban young residents, suggesting that new media exposure has an enormous effect on fast-food consumption in China [44].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we also found this negative correlation with some of the heart rate variability markers. According to these results, a body composition classified as unhealthy would be negative in an educational environment, directly affecting both the level of performance, as well as the adaptability of the student's parasympathetic system to adequately modulate the stressful situations that occur in this environment [63]. It seems necessary to find ways to implement school and extracurricular programs to improve the physical condition supported by a good nutritional strategy because non-healthy habits are enveloping children and youths in all demographic areas [64].…”
Section: Main Correlationsmentioning
confidence: 99%